EFISIENSI EKONOMI DAN DAYA SAING PADI ORGANIK DI KECAMATAN BANGUNREJO KABUPATEN LAMPUNG TENGAH - Agung Mubyarto; Muhammad Irfan Affandi; Umi Kalsum (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research aims to know the economic efficiency and competitiveness of organic rice farming in Bangunrejo District, Lampung Tengah Regency. This research was conducted in Bangunrejo District from September to October 2012, involving all of the twenty organic rice farmers planting rojo lele and melati varieties of riceas research respondents. Data were analized using Policy Analysis Matrix (PAM). The results showed that (1) the organic rice farming in Bangunrejo was produced efficiently in terms of private and social and (2) the organic rice farming in Bangunrejo District had competitiveness with value of PCR (Privat Cost Ratio) 0,197 and DRCR (Domestic Resource Cost Ratio) 0,204 Key words: competitiveness, efficiency, farmer, organic rice, PAM